2010
DOI: 10.1007/bf03259716
|View full text |Cite
|
Sign up to set email alerts
|

Change in Hematologic Indices over Time in Pediatric Inflammatory Bowel Disease Treated with Azathioprine

Abstract: Azathioprine leads to changes in mean corpuscular volume (MCV) and white blood cell (WBC) indices reflecting efficacy or toxicity. Understanding the interactions between bone marrow stem cells and azathioprine could highlight abnormal response patterns as forerunners for hematologic malignancies. This study gives a statistical description of factors influencing the relationship between MCV and WBC in children with inflammatory bowel disease treated with azathioprine. We found that leukopenia preceded macrocyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…This result is consistent with a previous study reporting that MCV values at 10 weeks after initiating thiopurine were significantly higher in patients with the heterozygous variant alleles of NUDT15 than in those without . Several studies suggest that thiopurine‐mediated inhibition of DNA synthesis in bone marrow precursor cells leads to megaloblastic erythropoiesis . MCV elevation above 7 fl is reported to be an indicator of optimal 6‐thioguanine nucleotide (6‐TGN) levels .…”
Section: Discussionsupporting
confidence: 91%
“…This result is consistent with a previous study reporting that MCV values at 10 weeks after initiating thiopurine were significantly higher in patients with the heterozygous variant alleles of NUDT15 than in those without . Several studies suggest that thiopurine‐mediated inhibition of DNA synthesis in bone marrow precursor cells leads to megaloblastic erythropoiesis . MCV elevation above 7 fl is reported to be an indicator of optimal 6‐thioguanine nucleotide (6‐TGN) levels .…”
Section: Discussionsupporting
confidence: 91%
“…Fifteen studies fulfilled the eligibility criteria . ‘Potentially’ eligible studies which were assessed and subsequently excluded are shown in http://onlinelibrary.wiley.com/doi/10.1111/bcp.12365/suppinfo.…”
Section: Resultsmentioning
confidence: 99%
“…Study findings were stratified for patients, according to disease stage, blood test results, patient characteristics, concomitant medications and median treatment duration. Clinical outcome definitions were clearly described in all but three studies . The characteristics and findings of the included studies are summarized in http://onlinelibrary.wiley.com/doi/10.1111/bcp.12365/suppinfo.…”
Section: Resultsmentioning
confidence: 99%
“…The pathophysiology of this phenomenon is not completely clear, but it has been suggested that it results from inhibition of DNA synthesis leading to megaloblastic erythropoiesis [14,15,17]. The prevalence and degree of macrocytosis may be dependent on the specific polymorphisms in the enzymatic pathway of thiopurine metabolism.…”
Section: Introductionmentioning
confidence: 97%
“…Alternative and widely available surrogate biomarkers that reflect intracellular thiopurine levels have thus been sought. Several hematologic biomarkers such as mean corpuscular volume (MCV), white blood cell, leukocyte count and platelet count have been evaluated for that purpose with conflicting results [11][12][13][14][15]. Guiding thiopurine treatment by appearance of leukopenia or macrocytosis is still a common practice [16].…”
Section: Introductionmentioning
confidence: 99%